Barriers evolving : reproductive isolation and the early stages of biological speciation - Jennings, Jackson Hubbard (2012)
The process of speciation can be complex and represents the ultimate basis for biodiversity on the planet Earth. The contribution of various intrinsic reproductive barriers and their underlying phenotypic mechanisms were studied using two Drosophila model systems: the cactophilic sister species Drosophila arizonae and D. mojavensis, from the deserts of Mexico and the Southwestern USA, and populations of the circumboreal, hydrophilic fly, Drosophila montana, from North America and Northern Europe. Levels of premating isolation between D. arizonae and D. mojavensis as well as between populations of D. montana were significant and sensitive to experimental design. Further investigations of intrinsic barriers to gene flow among populations of D. montana from Canada, Finland and the USA showed that different mechanisms (premating vs. postmating) act with different strengths depending on the populations. Premating isolation was significant between all populations and postmating isolation was strongest in crosses between American (Colorado) females and Canadian (Vancouver) males. This was found to be due to a postmating, prezygotic barrier; while sperm from Canadian males were successfully transferred and stored after matings with American females, the majority of these eggs were not fertilized. The last study in this thesis aimed to determine whether cuticular hydrocarbons might play a role in sexual selection in D. montana. The study revealed significant variation in cuticular hydrocarbons among populations and between the sexes, as well as correlations between particular principal components or individual hydrocarbon peaks and behavioural measurements relevant to sexual selection. These effects appeared to be strongest in the Canadian population of the species. Thus, cuticular hydrocarbons may be involved in sexual selection within and sexual isolation between populations, although more direct tests using manipulation of CHCs are still needed.